Imaging a Crustal Low‐Velocity Layer Using Reflected Seismic Waves From the 2014 Earthquake Swarm at Long Valley Caldera, California: The Magmatic System Roof?. Issue 8 (24th April 2018) - Nakata, Nori; Shelly, David R.
Abstract: The waveforms generated by the 2014 Long Valley Caldera earthquake swarm recorded at station MLH show clear reflected waves that are often stronger than direct P and S waves. With waveform analyses, we discover that these waves are reflected at the top of a low‐velocity body, which may be residual magma from the ∼767 ka caldera‐forming eruption. The polarity of the reflection compared to direct P and S waves suggests that the reflection is S P waves ( S from hypocenters to reflector and then convert to P waves to the surface). Because the wavefields are coherent among different earthquakes and hold high signal‐to‐noise ratios, we apply them to a wavefield migration method for imaging reflectors. The depth of the imaged magmatic system roof is around 8.2 km below the surface. This is consistent with previous studies. Even though we use only one station and waveforms from one earthquake swarm, the dense cluster of accurately located earthquakes provides a high‐resolution image of the roof. Plain Language Summary: The waveforms generated by the 2014 Long Valley Caldera earthquake swarm recorded at a station show clear reflected waves that are often stronger than direct P and S waves. We study these waves to identify their wave types and location of the reflectors using wavefield migration. The polarity of the reflection compared to direct P and S waves suggests that the reflection is S P waves ( S from hypocenters to reflector and then convert to P waves to the surface). The wavefields are coherent among different earthquakes and hold high signal‐to‐noise ratios, and we apply migration that provides much more accurate location of the reflector, which is a new insight for this volcano. The depth of the imaged magmatic system roof is around 8.2 km below the surface. Even though we use only one station and waveforms from one earthquake swarm, the dense cluster of accurately located earthquakes provides a high‐resolution image of the roof. This swarm is timely, and imaging of the magma‐related structure is a long‐standing topic. Key Points: Clear reflections are observed during 2014 Long Valley Caldera earthquake swarm We apply wavefield migration to the reflections to image the reflector using a single station The reflector is likely related to the top of the contemporary magmatic system at 8.2 km depth